Dissolution and biological assessment of cancer-targeting nano-ZIF-8 in zebrafish embryos - Mohd Abdul Kamal, Nurul Akmarina; Abdulmalek, Emilia; Fakurazi, Sharida; Cordova, Kyle E.; Abdul Rahman, Mohd Basyaruddin (ACS Publications, 2022)
Cancer-targeting nanotherapeutics offer promising opportunities for selective delivery of cytotoxic chemotherapeutics to cancer cells. However, the understanding of dissolution behavior and safety profiles of such nanotherapeutics is scarce. In this study, we report the dissolution profile of a cancer-targeting nanotherapeutic, gemcitabine (GEM) encapsulated within RGD-functionalized zeolitic imidazolate framework-8 (GEM⊂RGD@nZIF-8), in dissolution media having pH = 6.0 and 7.4. GEM⊂RGD@nZIF-8 was not only responsive in acidic media (pH = 6.0) but also able to sustain the dissolution rate (57.6%) after 48 h compared to non-targeting nanotherapeutic GEM⊂nZIF-8 (76%). This was reflected by the f2 value of 36.1, which indicated a difference in the dissolution behaviors of GEM⊂RGD@nZIF-8 and GEM⊂nZIF-8 in acidic media compared to those in neutral media (pH = 7.4). A dissolution kinetic study showed that the GEM release mechanism from GEM⊂RGD@nZIF-8 followed the Higuchi model. In comparison to a non-targeting nanotherapeutic, the cancer-targeting nanotherapeutic exhibited an enhanced permeability rate in healthy zebrafish embryos but did not induce lethality to 50% of the embryos (LC50 > 250 μg mL–1) with significantly improved survivability (75%) after 96 h of incubation. Monitoring malformation showed minimal adverse effects with only 8.3% of edema at 62.5 μg mL–1. This study indicates that cancer-targeting GEM⊂RGD@nZIF, with its pH-responsive behavior for sustaining chemotherapeutic dissolution in a physiologically relevant environment and its non-toxicity toward the healthy embryos within the tested concentrations, has considerable potential for use in cancer treatment.